A influência da religião nas roupas das mulheres protestantes pentecostais - Rossi, Luzemar Gomes (2015)
This work studies the historical evangelical presence in Brazil, with greater focus on female identity, allied customs and religious traditions associated with fashion. Furthermore, aims to understand, connected to fashion concepts, how evangelical women from 20 to 30, from Cristian Crongregation in Brazil or Good Assembly, choose their clothes to walk at parties spaces without forgetting the fashion or religious traditions.